The Effect of Different Cement Space on the Fracture Strength of Two Different Types Zirconium CAD/CAM Crowns - Dalia Abdalreda Sadiq1, Lateef Essa Alwan2 , Abdul Kareem J. Al-Azzawi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: Evaluate and compare the effect of three different cement space (50um, 70um and 90um) on the fracture strength of (vita zirconia crowns and Ips e-max Zir/cad zirconia crowns). Materials and Methods: An ideal prepared plastic dentoform model of a left maxillary first molar with deep chamfer finish line design was used as a pattern for fabrication master metal die. The model was scanned and the master metal die was milled by CAD/CAM system. Sixty crowns made from two different types of zirconium were fabricated on a metal die and were divided into two major groups (A and B)( 30 crowns for each group) according to the two different types of zirconium being used: Group A: fabricated with vita zirconium crowns ; Group B: fabricated with IPS e-maxZir/CAD crowns. Each group further subdivided into three subgroups (10 crowns constructed with 50 um cement space crowns ) , ( 10 crowns constructed with 70 um cement space crowns ) and (10 crowns constructed with 90um cement space crowns). Results: The results of this study presented that the highest mean value of fracture strength is recorded via Group A1 (3.767± 0.242), followed by GroupA2 (3.266 ± 0.116), Group A3 (2.883 ± 0.085), Group B1 (2.505± 0.155), Group B2 (2 ± 0.141) and Group B3(1.508 ± 0.151) respectively. The data were statistically analyzed using one-way ANOVA and HSD testes which revealed highly significant differences (p<0.01) among groups . independent sample t-test result revealed a statistically highly significant difference between subgroups. Conclusion: Vita zirconium crowns is more resistance to fracture than IPS e-max Zir/CAD. (50um cement space) have higher fracture strength than the others.